Modification of Human Capital and Technology Capital Measurement of Technology Sector Company Value - Dwi Jayanti; Romli Romli (Yayasan Riset dan Pengembangan Intelektual, 2024)
The COVID-19 epidemic has significantly impacted business performance across nearly all industries, including technology. Naturally, this also affects the fall in company values within this industry, as seen by the weak share price index for the entire year 2022. The purpose of this study is to investigate how technological and human capital affect a company's worth. The amount of personnel and training expenses incurred is compared to the sales value in this study to determine the human capital. Software growth is a key indicator of technology capital, whereas price-to-book value (PBV) measures a company's worth. All technology-related enterprises listed on the Indonesia Stock Exchange (BEI) comprise the research population. Purposive sampling is used in the sampling procedure. Multiple linear regression is the data analysis method employed in this study, and SPSS is the data processing software. According to the research's test results, there is no significant impact of either human capital or technical capital on the value of the organization. Concurrently, technology and capital have a big impact on a company's worth.